Efek program manajemen diri pada pasien penyakit paru obstruktif kronik : Systematis review - Harni Harniati; Syahrul Syahrul; Takdir Tahir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
ABSTRACTBackground: Self-management programs are very important in the care of patients with COPD as an independent intervention in an effort to improve health status. Aim: Of this systematic review is to find out the form of self-management intervention in COPD patients, an instrument to measure the outcomes of self-management and the effects of self-management programs in COPD patients. Methods: Used are electronic data bases from journals published through ProQuest, PubMed., And ScienceDirect. Results: Of a review of 9 selected journals stated that self-management programs had an influence on increasing lung capacity, exercise capacity and health-related quality of life compared to patients who experienced standard care. The research instrument was used to measure lung capacity using spirometry, Exercise capacity used a six-minute walking distance (6MWD), Incremental Shuttle Walk Test (ISWT) and the Endurance Shuttle Walk Test (ESWT), and health-related quality of life measured by St George Respiratory Questionnaire (SGRQ). The results showed that the effects of self-management programs benefited in the quality of care, reduced the number of days of hospital care and did not increase the number of deaths. Conclusion: Self-management programs in COPD patients provide the ability to manage disease so that it can increase lung capacity, exercise capacity and quality of life related to health. Keywords: Chronic obstructive pulmonary disease, exercise capasity, lung capacity self management program, quality of life